2023
DOI: 10.1371/journal.pone.0281470
|View full text |Cite
|
Sign up to set email alerts
|

Integrative systems biology analysis of barley transcriptome ─ hormonal signaling against biotic stress

Abstract: Biotic stresses are pests and pathogens that cause a variety of crop diseases and damages. In response to these agents, crops trigger specific defense signal transduction pathways in which hormones play a central role. To recognize hormonal signaling, we integrated barley transcriptome datasets related to hormonal treatments and biotic stresses. In the meta-analysis of each dataset, 308 hormonal and 1232 biotic DEGs were identified respectively. According to the results, 24 biotic TFs belonging to 15 conserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 173 publications
0
1
0
Order By: Relevance
“…MYC2, a bHLH transcription factor, is a JAZ-binding factor that targets jasmonate-responsive genes and regulates jasmonate-mediated processes [ 65 ]. The key genes in the JA biosynthetic pathway were screened out from hormonal treatments and biotic stress-related barley transcriptome datasets, and AOS , OPR3 , and LOX2 exhibited a significant positive correlation and interaction among themselves [ 66 ]. In this study, transcriptome sequencing showed that the expression levels of AOS , AOC , OPR , and JMT had the same pattern of expression, and JAZ and its binding factor MYC2 were significantly upregulated during bulbil initiation.…”
Section: Discussionmentioning
confidence: 99%
“…MYC2, a bHLH transcription factor, is a JAZ-binding factor that targets jasmonate-responsive genes and regulates jasmonate-mediated processes [ 65 ]. The key genes in the JA biosynthetic pathway were screened out from hormonal treatments and biotic stress-related barley transcriptome datasets, and AOS , OPR3 , and LOX2 exhibited a significant positive correlation and interaction among themselves [ 66 ]. In this study, transcriptome sequencing showed that the expression levels of AOS , AOC , OPR , and JMT had the same pattern of expression, and JAZ and its binding factor MYC2 were significantly upregulated during bulbil initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, RLK gene family is involved in the response to biotic and abiotic stresses 45 . It was reported that RLK/Pelles and TKLs are components of signaling networks that regulate the activation of the defense response 46 .…”
Section: Discussionmentioning
confidence: 99%